How Did Calgary Get Its River Parks? - Nelles, H. (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2005)
How did Calgary get its river parks? They certainly were not there to begin with. They weren't there as the city grew. They had to be built. As this paper shows, they were constructed relatively recently, and only after an astonishingly close brush with modernism, in which the land might have been dedicated to other dramatically different uses. Calgary's river parks appeared following a wrenching act of negation that bitterly divided the city in the mid-1960s. The organized women's movement of Calgary allied with urban elites, and the new planning bureaucracy and philanthropists combined to push the project forward—but not without the active co-operation of the river itself. The citizenry became so attached to their newly designed river that they were prepared to entertain a higher risk of flooding to keep it green. The result could have been quite different, and almost was. This paper maps a profound but nonetheless contingent shift in popular and political attitudes towards the river in urban life in Calgary that mirrored broader cultural reconsiderations of the environment and nature.